2021
DOI: 10.1149/1945-7111/abf064
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Route for Electrolytic Production of Very Branchy Copper Dendrites under Extreme Conditions

Abstract: Copper electrodeposition in a form of powder was examined using the pulsating overpotential (PO) regime from the sulfate electrolyte without or with an addition of various concentrations of chloride ions. Morphological and structural characteristics of the produced particles were analyzed by the scanning electron microscope (SEM) and the X-ray diffraction (XRD) method. The final morphology of Cu powders was determined with two parallel processes: a) suppression of hydrogen evolution reaction due to pause durat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…The synthesis of micro-/nanoscale metal materials has aroused tremendous interest due to their important role in photothermal, optoelectronics, catalysts, and sensors. In particular, the study of micro–nano structures of dendritic metal with multi-level branches has aroused considerable interest in the field of natural science. The fractal dendrites are extensively reported in the electrochemical deposition process. Studies show that metals, such as nickel (Ni), copper (Cu), zinc (Zn), and silver (Ag), could form fractal patterns with scale-invariant self-similarity under suitable conditions. , Among the metals, copper dendrites are receiving current attention in fractal theory and functional device aspects due to their excellent properties of high electric and thermal conductivity and a larger specific surface area. Recently, some studies have reported that the study of two-dimensional (2D) copper dendrites focuses on the 2D adjustment of the static interface. However, the copper dendritic growth under the action of the directional flow field and electric field is ignored. The regulation of dendrite growth under multi-field coupling is helpful to the new understanding of the electrochemical assembly of new functional materials.…”
Section: Introductionmentioning
confidence: 99%
“…The synthesis of micro-/nanoscale metal materials has aroused tremendous interest due to their important role in photothermal, optoelectronics, catalysts, and sensors. In particular, the study of micro–nano structures of dendritic metal with multi-level branches has aroused considerable interest in the field of natural science. The fractal dendrites are extensively reported in the electrochemical deposition process. Studies show that metals, such as nickel (Ni), copper (Cu), zinc (Zn), and silver (Ag), could form fractal patterns with scale-invariant self-similarity under suitable conditions. , Among the metals, copper dendrites are receiving current attention in fractal theory and functional device aspects due to their excellent properties of high electric and thermal conductivity and a larger specific surface area. Recently, some studies have reported that the study of two-dimensional (2D) copper dendrites focuses on the 2D adjustment of the static interface. However, the copper dendritic growth under the action of the directional flow field and electric field is ignored. The regulation of dendrite growth under multi-field coupling is helpful to the new understanding of the electrochemical assembly of new functional materials.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies reported that the morphology and microstructure of the resulting Cu coatings could be finely tuned by controlling plating parameters such as the applied potential, affecting the nucleation and growth rate of the deposit. 21,22 In particular, the unique anodic step in the PRC process is able to redistribute the adatoms on the cathode surface and result in the desorption of adatoms, which is an essential factor for morphology control. Kim et al explored the effect of anodic current on the microstructure of Cu coatings with or without additives, indicating the surface roughening by the anodic step.…”
mentioning
confidence: 99%